Analisis Implementasi Tanggung Jawab Sosial dan Lingkungan dalam Laporan Tahunan Terintegrasi PT Indonesia Infrastructure Finance Tahun 2023 - Lisa Ovelia; Ida Bagus Ketut Bayangkara (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to examine how corporate social and environmental responsibility is reflected in the 2023 integrated annual report of PT Indonesia Infrastructure Finance (IIF). Social and environmental responsibility is a crucial aspect in the development of a sustainable company and is increasingly emphasized in corporate financial and sustainability reporting. Using a qualitative approach, this research relies on secondary data obtained directly from IIF’s 2023 integrated annual report as the main source. The analysis focuses on assessing how well the company integrates social and environmental aspects into its business strategy and operations. The findings indicate that IIF has demonstrated a strong commitment to responsible, transparent, and sustainability-oriented operations. The annual report presents detailed information regarding the company’s policies, programs, and initiatives that support sustainable development, environmental protection, and contributions to society. IIF actively reports on the social and environmental impacts of its financing activities and implements Environmental, Social, and Governance (ESG) principles across all aspects of its operations. The study concludes that social and environmental responsibility is an integral part of PT Indonesia Infrastructure Finance’s business strategy. The company has successfully embedded sustainability aspects throughout its integrated annual report, reflecting its active role in creating long-term value not only for shareholders but also for society and the surrounding environment